Behavioural ecology of the caracal in the Kgalagadi Transfrontier Park, and its impact on adjacent small stock units - Bothma, Jacobus du P. (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.